Science-hobby book of archaeology - Fortiner, Virginia J (Lerner Publications Co. : Minneapolis, 1968)
Explains the principles and importance of archaeology as a science as well as some important sites, methods, and implements used on digs. Includes suggestions for the amateur to explore on his own or through one of the societies listed.
1962 ed. published under title: Archaeology as a hobby.
Keywords: Archaeology -- Juvenile literature